Fluctuating levels of personal role engagement within the working day: A multilevel study. (11th September 2017) - Fletcher, Luke; Bailey, Catherine; Gilman, Mark W.
Abstract: In this diary study, we examined a theoretical model in which the psychological conditions of meaningfulness, availability, and safety serve as mechanisms through which the work context during discrete situations within the workday influences "state" engagement. We further theorised that a person's "trait" level of engagement would exert cross‐level effects on the state level relationships. Multilevel analyses based on a sample of 124 individuals in six organisations and 1, 446 situational observations revealed that meaningfulness and availability (but not safety) mediated the relationships between perceptions of the work context and state engagement. High levels of trait engagement strengthened the within‐person relation between availability and state engagement, yet weakened the within‐person relation between meaningfulness and state engagement, suggesting two different processes may be at play. Overall, the findings advance our understanding of engagement as a multilevel and temporally dynamic psychological phenomenon and promote a contextually based HRM approach to facilitating engagement.